Encapsulation of Beta vulgaris extract by electrospraying and evaluation of antimicrobial potential - Marjana Radünz; Helen Cristina dos Santos Hackbart; Taiane Mota Camargo; Chirle de Oliveira Raphaelli; André Luiz Radünz; Eliezer Avila Gandra; Elessandra da Rosa Zavareze (Revista Ceres)
ABSTRACT Beets are rich in phenolic compounds and betalains that can be used as natural food colorings and have antimicrobial effects. However, these compounds are not very stable, and encapsulation can prolong their stability and action. The aim of this study was to investigate the antimicrobial activity of beetroot extract encapsulated by electrospraying with zein as wall material. The extract and capsules were characterized, as well as the encapsulation efficiency determined. Antibacterial activity was determined against gram-positive bacteria (Listeria monocytogenes, Staphylococcus aureus) and gram-negative bacteria (Salmonella Typhimurium, Escherichia coli) by the disk diffusion method using the minimum inhibitory concentration and the minimum bactericidal concentration. Encapsulation was efficient (92%) forming capsules with high thermal stability and spherical morphology with a regular surface. Beetroot extract and zein capsule with beetroot extract exhibited inhibition halos, inhibitory and bactericidal effects at a concentration of 200 mg mL-1against Salmonella Typhimurium.